Cinema at the 5th World Festival of Youth and Students in Warsaw (1955) - Pietrzak, Maciej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The article examines the cinematic aspects of the 5th World Festival of Youth and Students, held in Warsaw in 1955. It discusses initiatives related to the presence of filmmakers hosted in Poland, film events accompanying the Festival, the repertoire and screenings, as well as the logistical challenges associated with cinema infrastructure during the event. The study is based on an extensive collection of archival materials, primarily from the Archives of Modern Records (Archiwum Akt Nowych) in Warsaw. Among the analysed documents are correspondence, plans, and reports from the bodies responsible for organising the Festival’s cinematic components, which shed light on planning processes, the organisers’ ambitions, and the outcomes of their efforts. The corpus is complemented by press materials, enriching the analysis with additional contexts not available in the archival documentation.